FABLe: A Mobile Application to Assess and Build Foundational Literacy Skills for All Children, Including Children with Disabilities in India. (7th June 2023) - Misquitta, Radhika; Ghosh, Aditi
ABSTRACT: Fluency Assessment and Benchmarking for Literacy in Education (FABLe) is the first mobile application being developed for the assessment of foundational literacy skills in India. FABLe passages are currently available in English for Grades 2, 3 and 4, with plans to expand to other Indian languages. FABLe is designed to administer curriculum-based measures for reading (R-CBMs) that have been validated in the Indian context. This paper describes the preliminary benchmarking procedures being undertaken for the Indian student population and how FABLe screens for students at-risk for reading difficulties. Student performance data based on initial FABLe results are compared with international benchmarks and teacher perception data. Overall, FABLe scores are lower than international benchmarks. FABLe was able to accurately identify students needing additional support, with the majority of students identified at-risk falling below the 19th percentile in FABLe.